QUALITY EVALUATION OF VOCATIONAL SECONDARY SCHOOLS IN SLOVAKIA - NOVOTA, Marian; Michal, ZAN; Lukas, TKAC; KADNAR, Jozef; KLIEROVA, Martina; ZAHORCOVA, Erika; RIDZONOVA, Zuzana; STEFKOVA, Petra; PODARIL, Martin; Milan, STUR; PETNUCHOVA, Jana; HORNAKOVA, Veronika (Trends in education, 2012)
The article presents the evaluation of the quality of secondary schools in Slovakia. In Slovakia, there is no evaluation of the quality ranking of secondary schools and only comparison is made of quality university education. Evaluation of the quality of secondary schools and their graduates is a hot topic, but the rating system is not yet sufficiently resolved. An essential step is to create a functional system of evaluation of vocational education in Slovakia.
Keywords: indicator; evaluation; quality.